Kalman filter estimation of impedance parameters for medium transmission line - Siti Nur Aishah, Mohd Amin; Hamzah, Ahmad; Mohd Rusllim, Mohamed; Mohd Mawardi, Saari; Omar, Aliman (Universitas Ahmad Dahlan, 2018)
Accurate knowledge of impedance parameters in transmission line helps to improve the system efficiency and performance. Nowadays, the estimation of impedance parameters in transmission line has become possible with the availability of computational method. This paper aims to develop Kalman filter model by using Matlab simulink to estimate accurate values of resistance (R), reactance (X), and susceptance (B) in medium transmission line. The accuracy of the parameters can be improved by reducing the unknown errors in the system. To demonstrate the effectiveness of the Kalman filter method, a case study of simulated medium transmission line is presented and comparison between Kalman Filter (KF) and Linear Least Square (LLS) method is also considered to evaluate their performances.